2022
DOI: 10.1097/aci.0000000000000865
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the treatment of hemophagocytic lymphohistiocytosis and macrophage activation syndrome

Abstract: Purpose of reviewThe approach to treating patients with hemophagocytic lymphohistiocytosis (HLH) and macrophage activation syndrome (MAS) has shifted in recent years with the aim to limit exposure to genotoxic agents, such as etoposide, yet dampen hyperinflammation by targeting the activity of specific HLH/MAS-associated cytokines. In this review, we discuss recent efforts to reduce the dose of etoposide and/or incorporate cytokine-targeted therapies for the treatment of HLH/MAS.Recent findingsThere is emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…While the treatment of inflammation in fHLH has historically hinged on the use of genotoxic agents, understanding this pathophysiology at the cellular level creates opportunities for further development of rationally designed therapies targeting critical points in this cycle. Many such therapies have already shown promise in patients with fHLH and related immune dysregulation syndromes ( 59 ). Ongoing research into these mechanisms of immune dysfunction will support further clinical trials aimed at improving outcomes for patients with fHLH and related disorders of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…While the treatment of inflammation in fHLH has historically hinged on the use of genotoxic agents, understanding this pathophysiology at the cellular level creates opportunities for further development of rationally designed therapies targeting critical points in this cycle. Many such therapies have already shown promise in patients with fHLH and related immune dysregulation syndromes ( 59 ). Ongoing research into these mechanisms of immune dysfunction will support further clinical trials aimed at improving outcomes for patients with fHLH and related disorders of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Hemadsorption can also significantly reduce the high level of cytokines in the patient’s circulation ( 99 ). But unlike PE, hemadsorption does not require plasma separation and allows for simultaneous fluid removal ( 100 )( Figure 3 ). Recently, many reports have found that this treatment can rapidly reduce the level of IL-6 and IL-10, significantly improve hemodynamics, and without relevant associated adverse effects ( 101 , 102 ).…”
Section: The Attractive Therapeutic Approach To Prevent Mas In Covid-19mentioning
confidence: 99%
“…22 However, the diagnosis and treatment of familial HLH remain challenging. 24 Herein, we review the pediatric histiocytic disorders encountered in our hematopathology practice, focusing on the pathological features of morphology, immunophenotype, genetics, and clinical presentations (Tables 1 and 2).…”
Section: Introductionmentioning
confidence: 99%